POST-SURGICAL MEASURES DURING THE COVID-19 PANDEMIC - Suhaymi, Ery (Medicina Biomedica Journal, 2022)
Coronavirus Disease 2019 (COVID-19) has a very diverse clinical presentation ranging from asymptomatic, mild, moderate to severe symptoms and even death. The increase in the number of cases took place quite quickly and spread in a short time. The current COVID-19 pandemic has major consequences for healthcare services. Strict adherence to the use of Personal Protective Equipment (PPE), and environmental hygiene improves safety and prevents virus transmission. Postoperative management is an important phase for patients with suspected/confirmed COVID-19 because it can be associated with slower recovery, a longer length of stay, and more complications. Surgeons, nurses, and medical staff have equal responsibilities in postoperative management. Postoperative consultations can be carried out via telemedicine to perform follow-up surgery on patients with clinical COVID-19. The use of telemedicine-based services prevents the risk of potential exposure to medical personnel. Taking the recommended steps in general surgical services can optimize the health services provided to confirmed COVID-19 patients and reduce the risk of occupational transmission to other patients and health professionals